Antibacterial activity of underutilized "Curcuma species of the Philippines - Marcon, Gesselle R.
Plant oils and extracts have been used in traditional medicine due to their therapeutic potential. Various extracts of plants are being investigated as possible sources of natural products for applications in pharmaceuticals and alternative medicine. Curcuma species is the focus of this study. Various species of this family are used in traditional medicine for the treatment of arthritis, scabies, and other skin related diseases (Kamazeri, et al, 2012) The ethanolic extract of three underutilized Curcuma species in the Philippines were tested for their antibacterial activity using disk diffusion assay. Phytochemical screening tests were then done to determine the compounds present in the extracts. Results showed that the three species displayed varying degrees of antimicrobial activity against Gram negative and Gram positive bacteria. Curcuma zedoaria extracts possess strong inhibition against B. subtilis with a value of 17.68 ± 6.66 while Curcuma aeruginosa extracts possess strong inhibition against E. coli with a value of 16.68 ± 5.77. Doxycycline was used as positive control in all bacteria showing strongest inhibition against S. aureus with a value of 36.00 ± 0.00. On the other hand, Curcuma mangga exhibited partial inhibition against the bacteria. Phytochemical screening tests showed that alkaloids, flavonoids, terpenoids, phenols, and saponins are mostly present in the three species. The extracts were subjected to thin layer chromatography and results showed that curcumin, the most active compound among the species, was present in all extracts.